Longer term outcomes with single‐agent belantamab mafodotin in patients with relapsed or refractory multiple myeloma: 13‐month follow‐up from the pivotal DREAMM‐2 study. Issue 22 (27th July 2021) - Lonial, Sagar; Lee, Hans C.; Badros, Ashraf; Trudel, Suzanne; Nooka, Ajay K.; Chari, Ajai; Abdallah, Al‐Ola; Callander, Natalie; Sborov, Douglas; Suvannasankha, Attaya; Weisel, Katja; Voorhees, Peter M.; et al.
Abstract : Background: On the basis of the DREAMM‐2 study (ClinicalTrials.gov identifier NCT03525678), single‐agent belantamab mafodotin (belamaf) was approved for patients with relapsed or refractory multiple myeloma (RRMM) who received ≥4 prior therapies, including anti‐CD38 therapy. The authors investigated longer term efficacy and safety outcomes in DREAMM‐2 after 13 months of follow‐up among patients who received belamaf 2.5 mg/kg. Methods: DREAMM‐2 is an ongoing, phase 2, open‐label, 2‐arm study investigating belamaf (2.5 or 3.4 mg/kg) in patients with RRMM who had disease progression after ≥3 lines of therapy and were refractory to immunomodulatory drugs and proteasome inhibitors and refractory and/or intolerant to an anti‐CD38 therapy. The primary outcome was the proportion of patients that achieved an overall response, assessed by an independent review committee. Results: As of January 31, 2020, 10% of patients still received belamaf 2.5 mg/kg. Thirty‐one of 97 patients (32%; 97.5% confidence interval [CI], 21.7%‐43.6%) achieved an overall response, and 18 responders achieved a very good partial response or better. Median estimated duration of response, overall survival, and progression‐free survival were 11.0 months (95% CI, 4.2 months to not reached), 13.7 months (95% CI, 9.9 months to not reached), and 2.8 months (95% CI, 1.6‐3.6 months), respectively. Response and survival outcomes in patients who had high‐risk cytogenetics or renal impairment were consistent with outcomes in the overall population. Outcomes were poorer in patients with extramedullary disease. In patients who had a clinical response and prolonged dose delays (>63 days; mainly because of corneal events), 88% maintained or deepened responses during their first prolonged dose delay. Overall, there were no new safety signals during this follow‐up. Conclusions: Extended follow‐up confirms sustained clinical activity without new safety signals with belamaf in this heavily pretreated patient population with RRMM. Abstract : Extended follow‐up of patients enrolled in the ongoing phase 2 DREAMM‐2 study confirms sustained clinical activity without new safety signals in patients with relapsed or refractory multiple myeloma who receive belantamab mafodotin 2.5 mg/kg every 3 weeks. These data show that belantamab mafodotin has the potential to shift the treatment paradigm in this heavily pretreated, anti‐CD38 monoclonal antibody–exposed patient population, which has a poor prognosis and few alternative treatment options.